Optimal daratumumab-based regimen for patients with newly diagnosed and previously untreated multiple myeloma: systematic review and component network meta-analysis - Xiaohua Huang; Jia Zhou; Yuxiao Qian; Jing He; Lu Yang; Zhigang Wang; Diu Wei; Mengjie Li; Wei Ma; Haiyan Lang (Systematic Reviews)
Abstract Background Daratumumab (Dara)-based regimens have been investigated in randomized controlled trials (RCTs) involving patients with newly diagnosed and previously untreated multiple myeloma (NDMM), but the optimal daratumumab-based regimen remains unclear. This study compares the efficacy of daratumumab-containing regimens for NDMM patients and explores optimal combinations. Methods Databases were searched from inception until February 29, 2024. Trials comparing regimens with and without daratumumab, as well as their mutual comparisons, were included. Random effects models for serious adverse events (SAEs) and fixed effects models for other outcomes were utilized in both network meta-analysis (NMA) and component NMA (CNMA), with pooled effects estimated. The efficacy of all possible combinations of daratumumab with other drugs was assessed. Results A total of 17 trials were included, enrolling 7261 patients, of whom 2083 were treated with daratumumab. The optimal regimens for different outcomes were identified as follows: Dara-bortezomib (V)-melphalan (M)-corticosteroids (D) (Dara-VMD) showed the best results for both overall response rate (ORR) [RR = 1.97; 95% CI: 1.42 to 2.75; I 2 = 0.00%; 16 trials; 7136 participants; P = 0.00] and ≥ very good partial response (≥ VGPR) [RR = 7.46; 95% CI: 4.10 to 13.46; I 2 = 23.96%; 16 trials; 7118 participants; P = 0.00]; Dara-V-thalidomide (T)-D (Dara-VTD) was optimal for achieving ≥ complete response (≥ CR) [RR = 14.15; 95% CI: 3.74 to 53.52; I 2 = 0.00%; 17 trials; 7261 participants; P = 0.00]. The individual effects of daratumumab were calculated as follows: [ORR: RR = 1.14; 95% CI: 1.08 to 1.21; I 2 = 0.00%; 16 trials; 7136 participants; P = 0.00; ≥ VGPR: RR = 1.46; 95% CI: 1.36 to 1.58; I 2 = 23.96%; 16 trials; 7118 participants; P = 0.00; ≥ CR: RR = 1.77; 95% CI: 1.55 to 1.99; I 2 = 0.00; 17 trials; 7261 participants; P = 0.00; progression-free survival (PFS): hazard ratio (HR) = 0.53; 95% CI: 0.43 to 0.65; I 2 = 0.00%; 13 trials; 5977 participants; P = 0.00; overall survival (OS): HR = 0.68; 95% CI: 0.58 to 0.79; I 2 = 28.97%; 12 trials; 5977 participants; P = 0.00]. Additionally, the optimal regimens for PFS and OS were Dara-lenalidomide (R)-D [HR = 0.37; 95% CI: 0.23 to 0.61; I 2 = 0.00%; 13 trials; 5977 participants; P = 0.00] and Dara-VRD [HR = 0.40; 95% CI: 0.19 to 0.85; I 2 = 28.97%; 12 trials; 5977 participants; P = 0.02], respectively. Finally, CNMA indicated that Dara-VRD, Dara-carfilzomib (K)-RD, Dara-RD, and Dara-cyclophosphamide (C)-RD were four regimens, which could improve remission rate, and reduce death or progression during induction and prolong lifetime. Conclusions Dara-VRD, Dara-KRD, Dara-RD, and Dara-CRD are optimal daratumumab-based regimens for patients with newly diagnosed and previously untreated multiple myeloma.